Pengaruh Durasi Waktu Pendaftaran terhadap Kepuasan Pasien antara Pendaftaran Online dan Offline - Jaka Prasetya; Sylvia Anjani; Faik Agiwahyuanto (Politeknik Negeri Jember, 2022)
Long waiting times affect the pharmacy's efficiency and cause patients' dissatisfaction. The queue system at Puskesmas that does not perform maximally can be caused the Puskesmas’s perform ineffectively. For each Puskesmas it is a challenge to decrease the patients’ waiting time, to provide timely care and to improve the patient’s satisfaction. Long waiting times are the most important complaint in patient satisfaction surveys. The objective of this article was analysis of the effect of registration time duration on patient satisfaction between online registration of Puskesmas Without Queues (PUSTAKA) and offline registration at Community Health Centers (Puskesmas) Semarang. The design of this study was a correlation study with a cross sectional approach. The populations were 150 patients who registered online and offline Puskesmas Semarang on average in December 2019. The sample were 109 patients. Data analysis procedures to test the duration of time using different tests (t independents samples) while the analysis of the effect of registration time duration towards patient satisfaction between online registration of Puskesmas Without Queues (PUSTAKA) and offline registration at Community Health Centers (Puskesmas) Semarang uses linear regression multiple. There is an effect of time duration on patient satisfaction